DISCOVERING PERSONS WITH DISABILITIES PHYSICAL BARRIERS IN ACCESSING HEALTHCARE-BUILT ENVIRONMENT - AWANG @ MAT NAWI, DR. NURATIQAH AISYAH; CHUA, SHIRLEY JIN LIN; ALI, AZLAN SHAH; AZMI, AMALINA; SELVI NAICKER, AMARAMALAR (Journal of Surveying, Construction and Property, 2024)
Several studies have highlighted the dissatisfaction of Persons with Disabilities (PWDs) with the facilities and services in various built environments, yet limited research has focused on the healthcare-built environment. This study aims to identify the physical barriers faced by PWDs in accessing healthcare facilities in Malaysia. A qualitative approach was employed, involving semi-structured interviews and the analysis of complaint records. Four hospital engineers were selected through purposive sampling, and data from the facility management complaint database were extracted. Content analysis was conducted using Microsoft Word and Excel. Findings revealed that PWD toilets had the highest frequency of breakdowns and complaints, highlighting them as a key area for improvement. While breakdowns in most facilities were reported as low to moderate (2-10 times per month), issues with covered walkways were also noted, indicating broader accessibility concerns. PWD-related complaints were relatively low, reflecting their minority status in the population. The identified barriers related to maintenance, access to information, building use, and facility provision, impacting safety, accessibility, and overall ease of use. Establishing comprehensive data will help stakeholders understand physical barriers and develop strategies for improvement, ensuring equal access to healthcare facilities for PWDs. Future research on maintenance policies and their impact on PWDs is essential for fostering a more inclusive healthcare environment.